Thread Lifting Techniques for Facial Rejuvenation and Recontouring - Samizadeh, Souphiyeh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This book provides a practical guide to thread lifting techniques for facial rejuvenation and re-contouring of the face. It systematically describes the evidence base for the use of a range of available techniques for thread lifting, providing detailed guidance on how to analyse the face, take clinical photographs and correctly apply polydioxanone (PDO) threads, polycaprolactone (PCL) threads, Silhouette Soft threads and Aptos threads. Thread Lifting Techniques for Facial Rejuvenation and Recontouring comprehensively covers the use of a range of non-surgical techniques for thread lifting and provides a valuable resource for a range of medical professionals and trainees including dermatologists, plastic surgeons, nurses and aesthetic doctors seeking an up-to-date resource on the topic.
Thread lift history -- Various threads available -- Facial assessment and analysis -- Facial sexual dimorphism -- Treatment planning: Caucasian, Asian -- PDO Threads -- PCL Threads -- Silhouette soft threads -- Aptos threads -- Other threads -- Facial contouring and rejuvenation: Asian Face -- Facial contouring and rejuvenation: Caucasian face -- Complications prevention -- Complications management -- Combination with other treatments. .
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Dermatology; Surgery; Dermatology; Surgery